2015
DOI: 10.1002/cphc.201500783
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Porphyrin–Anionic Surfactant Mixtures for the Promotion of Self‐Organized 1:4 Ion Pairs in Water with Strong Aggregation Properties

Abstract: We performed a systematic study on the spectroscopic and aggregation properties of stoichiometric mixtures (1:4) of the tetracationic meso-tetrakis(4-N-methylpyridinium)porphyrin (H2 TMPyP) and three sodium alkylsulfate surfactants (tetradecyl, hexadecyl, and octadecylsulfate) in an aqueous solution. The objective was to build a supramolecular aggregate, which would favor the internalization of tetracationic porphyrins in cells without chemical modification of the structure of the porphyrin. We show that stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…In a different approach, sodium alkyl sulfate surfactants with different alkyl chain lengths (C 14-16-18 OSO 3 Na) have been mixed in a stoichiometric ratio with positively charged meso-tetrakis(4-N-methylpyridinium)porphyrin in water to obtain supramolecular aggregates [62]. The aim of the work was to improve the cellular uptake of the cationic porphyrin, and consequently its biological activity as anticancer agents.…”
Section: Effects Of Chemical External Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…In a different approach, sodium alkyl sulfate surfactants with different alkyl chain lengths (C 14-16-18 OSO 3 Na) have been mixed in a stoichiometric ratio with positively charged meso-tetrakis(4-N-methylpyridinium)porphyrin in water to obtain supramolecular aggregates [62]. The aim of the work was to improve the cellular uptake of the cationic porphyrin, and consequently its biological activity as anticancer agents.…”
Section: Effects Of Chemical External Stimulimentioning
confidence: 99%
“…Modeling of the cationic porphyrin–C 18 OSO 3 Na ion pair structure in water reported by Pratviel et al Reprinted with permission from [62]. Copyright 2015, Wiley.…”
Section: Figures and Schemesmentioning
confidence: 99%
“…[15,[22][23][24] The morphologies of porphyrinoid assembly are controlled by polarity, pH, concentration of porphyrin, porphyrin structure, aging time and counter ions of inorganic salt. [25][26][27][28] Sakuma et al have demonstrated the synthesis of nanocubes, nanorods and microrods from free base porphyrin [meso-tetra(4-carboxyphenyl)porphyrin] for modify-ing the photophysical properties. [29] Different types of ZnTPyP nano-aggregates such as nanotubes, nanorods and nanofibers with variable length were synthesized by regulating the aging time and counter ion concentration.…”
Section: Introductionmentioning
confidence: 99%
“…J‐type and H‐type aggregated porphyrin exhibit red and blue absorption shift from their monomeric entity, respectively and the J‐type aggregation exhibits the faster energy transfer . The morphologies of porphyrinoid assembly are controlled by polarity, pH, concentration of porphyrin, porphyrin structure, aging time and counter ions of inorganic salt . Sakuma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods can be used to assemble porphyrin derivatives, as template-directed, surfactant-assisted, and deposition methods or pH-induced self-assembly protocol, among others [15][16][17][18][19][20][21][22][23][24][25][26]. Over the course of our studies focused on the development of amphiphilic porphyrin-based supramolecular systems, we largely used the "good-bad" solvent self-assembling method, by which macrocycles are at first molecularly dissolved in a good solvent and then a bad solvent is added to trigger the aggregation process.…”
Section: Introductionmentioning
confidence: 99%